Part 1: development of a base-free methodology for the NHC-catalyzed intermolecular stetter reaction. Part 2: Chiral anion mediated asymmetric stetter reaction - Choo, Joy En (2010)
Part I: Development of a base-free methodology for the NHC- catalyzed Intermolecular Stetter Reaction. We succeeded in developing a base-free methodology for the NHC-catalyzed intermolecular Stetter reaction by employing CsF as a dual Lewis acid/base activating reagent, achieving the desired 1,4-dicarbonyl structural scaffold under ultrasonication reaction condition. Generally, moderate to excellent yields were obtained. Yields were especially good when highly reactive Michael acceptors were employed in conjuction with an aromatic carbinol carrying electron withrdrawing subtituents. In all cases, this transformation only generated the desired 1,4-dicarbonyl product with no observation of benzoin products as commonly observed with other reaction routes. Unfortunately, sterically hindered carbinols and α-substituted Michael acceptors are not well tolerated in this reaction. Part II: Chiral anion mediated Stetter Reaction. A preliminary study was carried out on the feasibility of inducing an enantioselective Stetter reaction by chiral anions. Several reports show that highly efficient enantioselective induction could be obtained with chiral cations and anions when there exists a tight ion contact pair in the chemical transformation. We propose that such intimate ion pairing might be possible in the key breslow intermediate for chiral anion mediated enantioselectivity in the Stetter reaction.